BENTUK-BENTUK ETIKA KOMUNIKASI DAKWAH DALAM AL-QUR’AN - Aip Nuralim; Canra Krisna Jaya (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Certain words are seen as very effective [having power] in influencing or changing human behavior. Because psychologically, language has a very significant role in controlling or changing human behavior. This interaction can then be used as a guide by communicators [dai] in spreading the message of Islam to Mad'u. The most important meaning of communication is that someone gives an interpretation of another person's behavior [which takes the form of speech, bodily movements or attitudes], the feelings that that person wants to convey. The person concerned then reacts to the feelings that the other person wants to convey. To produce positive interactions in the da'wah communication process, a da'wah communicator must pay attention to what he speaks and says. This article discusses ethical forms of da'wah communication from the perspective of the Koran. Specific terms used by the Qur'an to explain forms of communication include: qawlan adhima, qawlan baligha, qawlan karima, qawlan layyina, qawlan maisura, qawlan ma'rufan, qawlan sadidan, qawlan tsaqila. Therefore, the description of da'wah communication contained in the Al-Quran can be used as a basis for practicing good and polite communication patterns in social, political and other aspects.